Pengaruh Pelaksanaan Program P5 dan Budaya Sekolah Terhadap Kedisiplinan Siswa di SMP Negeri 8 Palembang - Nina Veranica; Tri Widayatsih; Sri Wahyu Indrawati (CV. ULIL ALBAB CORP, 2025)
This study aims to determine the effect of the implementation of the P5 program and school culture on student discipline at SMP Negeri 8 Palembang. This type of research is quantitative research. The sample in this study was 185 students of SMP Negeri 8 Palembang. Data collection techniques used questionnaires. Data analysis techniques used quantitative descriptive analysis techniques, simple regression and multiple regression tests. The results of this study state that 1) there is a significant effect of the implementation of the P5 program on student discipline at SMP Negeri 8 Palembang; 2) there is a significant effect of school culture on student discipline at SMP Negeri 8 Palembang 3) there is a significant effect together of the implementation of the P5 program and school culture on student discipline at SMP Negeri 8 Palembang